2021
DOI: 10.1088/1755-1315/735/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of some pesticides and bioagents against Parlatoria date scale Parlatoria blanchardi Targ (Homoptera: Diaspididae) on date palm Phoenix dactylifera

Abstract: This study conducted to evaluate the effectiveness of some pesticides and Entomopathogenic fungi Beauveria bassiana (Naturalis-L) and Entomopathogenic bacteria Bacillus thuringienesis (Antario KAB) in different methods (irrigation, injection and spray) against Parlatoria blanchardi Targ on date palm in Ghammas / Al-Shamiya District / Al-Qādisiyyah Governorate / Iraq during agriculture season 2019-2020. The results showed that the pesticide TIAM 25% WG was more significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…A similar conclusion on the positive interaction of mixtures was reported by Abdulwahid and Mohammadali (2021). According to these authors, the use of pesticide mixed with bioagent showed that the treatment TIAM 25% WG + B. bassiana sprayed on a palm in the field was significantly different from single treatments, and the efficacy reached 82% after 7 and 14 days of treatment.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…A similar conclusion on the positive interaction of mixtures was reported by Abdulwahid and Mohammadali (2021). According to these authors, the use of pesticide mixed with bioagent showed that the treatment TIAM 25% WG + B. bassiana sprayed on a palm in the field was significantly different from single treatments, and the efficacy reached 82% after 7 and 14 days of treatment.…”
Section: Resultssupporting
confidence: 79%
“…Many authors have reported increasing efficacy, accompanied by high toxic effects of microbial insecticides the last day after treatment against several insect pests (Atanasova and Vasilev 2020;Fabrice et al 2020;Abdulwahid and Mohammadali 2021). For period showed that the significantly highest reduction of products of natural origin was achieved after the combined treatment of Aminogreen 24 + Naturalis (49.0%), followed by Naturalis (44.0%) and Nitrogreen + Naturalis (43.6%) (F 8,5 = 29.290; p < 0.033).…”
Section: Resultsmentioning
confidence: 99%